Plädoyer für einen "Rentenfonds Deutschland": Warum ein kapitalgedeckter Investitionsfonds ein wichtiger Beitrag zu mehr Generationengerechtigkeit sein könnte - Volker Brühl (Goethe University Frankfurt, Center for Financial Studies (CFS), 2018)
The German government has recently adopted a reform package for the statutory pension insurance scheme to ensure that the pension level will not fall below 48% and that the contribution rate will not exceed 20% up to 2025. In addition, there are planned improvements in maternal pensions, pensions for people with reduced earnings capacity and relief for low-income earners. The total extra cost of these measures is estimated at approximately EUR 32bn, to be financed by funds of the statutory pension system and by increased federal subsidies. It is currently unclear how the German pay-as-you-go pension system will be reformed for the period after 2025. The author suggests establishing a "Pension Fund Germany" as a capital-backed fund with a highly diversified investment portfolio. A German sovereign wealth fund of this kind could make an important contribution to greater intergenerational equity. Financing could be provided by, for example, retaining part of the solidarity surcharge on German income tax rather than abolishing it entirely, as is currently envisaged.
urn:nbn:de:hebis:30:3-474123
Keywords: H54; H55; 330